Sundanese Sufi and Religious Diversity in the Archipelago: The Pluralistic Vision of Haji Hasan Mustapa (1852-1930) - Rohmana, Jajang A (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2016)
The paper aims to analyze moderate understanding of Haji Hasan Mustapa on religious diversity in the archipelago. He is a greatest Sundanese poet who has studied in Mecca and served as Hoofd Penghulu of Kotaraja Aceh and Bandung in the colonial era. This study is focused on sufism and religious diversity, Mustapaâs scholarship, and on his pluralistic vision, using intertextual studies and semantic analysis. This research argues that Mustapa has tolerance and moderate understanding similarly with Ibn âArabiâs thought. He uses kernel and husk as symbolic images which expressed using natural richness of Sundanese culture for demonstrating his religious conviction that rasa is the kernel of all religions. This study is significant for strengthening the discourse of religious pluralism from sufi perspective in the archipelago which cannot be separated from the chain of Islamic intellectual network. This research has also a significant impact on Chittickâs assumption about the depth of sufi poetry which mostly reveal their tolerance views on religious diversity living in harmony. Keywords: poetry, sufism, Sunda, religious diversity